New methodology for Emiliania huxleyi cultivation: Mediterranean seawater vs. artificial seawater - Vera-Lozano, José Antonio; Toro Pineda, Iván; Ramírez, Librada; Lozano-Francisco, María del Carmen; Segovia-Azcorra, María (My University, 2023)
The use of Emiliiania huxleyi in research requires the elaboration of artificial seawater for its cultivation. This entails a significant expenditure of time and resources, sometimes requiring days of work for its preparation. As an alternative, the possibility of using Mediterranean seawater for the cultivation of the Norwegian Sea strain RCC 1226 is proposed in this work.
Keywords: Cocolitóforos - Crecimiento; Protozoos; Emiliania huxleyi; Culture medium; Growth dynamic